Pengembangan modul berbasis discovery learning terintegrasi sains pada materi kesetimbangan kimia - Riska, Cut Safrida; Sutiani, Ani (ARKA INSTITUTE, 2022)
This study aims to analyze the feasibility and student responses, from the development of a discovery learning- based module that integrated with scientific literacy. Subject of this research is module based on the discovery learning learning model which is integrated with scientific literacy. Object of this research is material of chemical equilibrium. This type of research is development that refers to the ADDIE model. This study uses non-test instruments, that used in the form of Validation Sheets that have met the BSNP standards, namely aspects of the feasibility of content, presentation, language and graphics by validator and student response questionnaire sheets with a scale of five categories. The validation feasibility result show that all aspects of the material, graphics and language are declared feasible and valid. Thus, it can be concluded that the development of discovery learning-based modules is integrated with scientific literacy in chemical equilibrium material.